Use of physician assistants in a managed health care system. - Hooker, R S (1991)
Kaiser Permanente Northwest Region is a prepaid group practice health maintenance organization. Among the employed are 65 physician assistants (PAs) who work in primary care and in certain subspecialties. Kaiser Permanente was one of the first managed health care systems to use PAs and has contributed to the historical documentation of their effectiveness. An interest in experimenting with new forms of health care delivery as well as enabling State legislation has contributed to an expanded role for nonphysician providers. Together with nurse practitioners, PAs comprise 20 percent of the primary care staff and write 25 percent of the prescriptions for the membership. The use of PAs in managed health care settings will likely increase to meet growing primary care demands. Analysts have found the cost of a PA ranges from 25 percent to 53 percent of the cost of a physician. PAs are capable of providing care for 86 percent of the diagnoses seen in outpatient primary care setting, and patient acceptance is high.